My Grecian tragedy - Nelson, Tim (My University, 2008)
Paper presented at the 2008 Nature, Art, Self Conference by Tim Nelson (University of Wisconsin-River Falls) in which he discusses the estranged relationship between Helen of Troy and Menelaus.
4 p.
Keywords: Mythology, Greek; Greek mythology; Paris; Helen of Troy (Greek mythology); Paris (Legendary character); Man-woman relationships; Homer; Menelaus (Greek mythology); Helen of Troy; Menelaus; Iliad; Husband and wife